Writing Histories of Rhetoric. - Vitanza, Victor J. (Southern Illinois University Press, 2013)
This collection of essays, edited by Victor J. Vitanza, is a historiography of rhetoric, summarizing what has recently been accomplished in the revision of traditional histories of rhetoric and discussing what might be accomplished in the future. Featuring a variety of approaches-classical, revisionary, and avant-garde-it includes articles by Janet M. Atwill, James A. Berlin, William A. Covino, Sharon Crowley, Hans Kellner, John Poulakos, Takis Poulakos, John Schilb, Jane Sutton, Kathleen Ethel Welch, Lynn Worsham, and Victor J. Vitanza. In the first essay, Sharon Crowley identifies the m.